1987
DOI: 10.1056/nejm198702193160803
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Amoxicillin with and without Decongestant-Antihistamine for Otitis Media with Effusion in Children

Abstract: In a randomized, double-blind, placebo-controlled trial involving 518 infants and children who had otitis media with effusion ("secretory" otitis media), we evaluated the efficacy of a two-week course of amoxicillin (40 mg per kilogram of body weight per day) with and without a four-week course of an oral decongestant-antihistamine combination. Among the 474 subjects who were evaluated at the four-week end point, the rate of resolution of middle-ear effusion was twice as high in those treated with amoxicillin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
1
4

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(53 citation statements)
references
References 16 publications
0
48
1
4
Order By: Relevance
“…We excluded Mandel et al [29] because it had several scientific lapses, including unexplained and undisclosed departures from the study protocol which inflated the antibiotic efficacy by some 53%. They did not use objective endpoint measures and did not correct for the unexplained distribution of poor prognostic factors unfavorable to the placebo control group.…”
Section: Cantekin/mcguirementioning
confidence: 99%
See 3 more Smart Citations
“…We excluded Mandel et al [29] because it had several scientific lapses, including unexplained and undisclosed departures from the study protocol which inflated the antibiotic efficacy by some 53%. They did not use objective endpoint measures and did not correct for the unexplained distribution of poor prognostic factors unfavorable to the placebo control group.…”
Section: Cantekin/mcguirementioning
confidence: 99%
“…They did not use objective endpoint measures and did not correct for the unexplained distribution of poor prognostic factors unfavorable to the placebo control group. Mandel et al [29] and the analysis of three other NIH-funded clinical trials of antibiotic efficacy in the treatment of otitis media were found to be 'less than objective' and biased in favor of antibiotic efficacy, as stated in a report (December 1990) of the Office of Scientific Integrity of the NIH [30]. We have earlier published [6] in JAMA a reanalysis of Mandel et al [29].…”
Section: Cantekin/mcguirementioning
confidence: 99%
See 2 more Smart Citations
“…Nasal and oral decongestants, administered either alone or in combination with an antihistamine, are currently among the most popular medications for treatment of AOM and OME. Unfortunately, decongestants and antihistamines were shown to be ineffective in two large-scaled clinical trials in infants and children with OME [18,19]. Antihistamines may be effective for those patients who have allergic rhinitis causing eustachian tube dysfunction.…”
Section: Decongestants and Antihistaminesmentioning
confidence: 99%